2021
DOI: 10.5334/cstp.369
|View full text |Cite
|
Sign up to set email alerts
|

The Diversity of Participants in Environmental Citizen Science

Abstract: Reported benefits of environmental citizen science include the collection of large volumes of data, knowledge and skills gained by participants, local action, and policy influence. However, it is unclear how diverse citizen science participants are, raising concerns about representativeness of data and whether individual, societal, and environmental benefits are evenly distributed. We surveyed 8,220 people representing a cross section of the population in Great Britain to ask whether they had participated in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
132
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(142 citation statements)
references
References 50 publications
6
132
3
1
Order By: Relevance
“…People identifying as being from minority ethnic groups were overrepresented in these groups compared with the overall sample of survey respondents. This is in line with previous research, which has shown that people from minority ethnic groups are more likely to participate in citizen science when they are in education (Pateman et al 2021) and when they are recruited via direct requests to participate or through community representatives (Sorensen et al 2019).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…People identifying as being from minority ethnic groups were overrepresented in these groups compared with the overall sample of survey respondents. This is in line with previous research, which has shown that people from minority ethnic groups are more likely to participate in citizen science when they are in education (Pateman et al 2021) and when they are recruited via direct requests to participate or through community representatives (Sorensen et al 2019).…”
Section: Discussionsupporting
confidence: 92%
“…Of these initial survey respondents, 613 individuals had participated in citizen science and were, therefore, asked about their motivations for participating. In the participant group, the proportion of people in different demographic groups was determined by both the makeup of the initial sample (i.e., representative of the wider population) and the propensity of different groups to participate in citizen science (see Pateman et al 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasingly, the citizen science community is formulating the demand and desire to make the group of participants from science and society as diverse as possible, e.g., [5,6]. Cooper et al (2020) have just brought the discussion about the claims to inclusiveness and terminology of citizen science into focus [7].…”
Section: Inclusiveness and Diversity In Citizen Science Projectsmentioning
confidence: 99%
“…CS combines the objective of informing and training the public on certain topics and providing data on that topic to the scientists. The advantage of CS with respect to “traditional science” is to allow the collection of a large amount of data over wide areas, which would otherwise not be possible if conducted by paid professionals [ 2 ].…”
Section: Introductionmentioning
confidence: 99%